2006
DOI: 10.1093/carcin/bgi379
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Wnt inhibitory factor-1 (WIF1) expression by epigenetic silencing is a common event in breast cancer

Abstract: The Wnt signaling pathway is a powerful and prominent oncogenic mechanism dysregulated in numerous cancer types. While evidence from transgenic mouse models and studies of human tumors clearly indicate that this pathway is of likely importance in human breast cancer, few clues as to the exact molecular nature of Wnt dysregulation have been uncovered in this tumor type. Here, we show that the Wnt inhibitory factor-1 (WIF1) gene, which encodes a secreted protein antagonistic to Wnt-dependent signaling, is target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
124
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(134 citation statements)
references
References 43 publications
10
124
0
Order By: Relevance
“…This inhibition of cell proliferation is consistent with the in vitro inhibition of cell growth by WIF1 as previously shown for other cancer cell lines (Ai et al, 2006;Kim et al, 2007;Kansara et al, 2009;Kawakami et al, 2009;Tang et al, 2009). However, in previous studies, WIF1 overexpression was shown to induce G 1 arrest in HPVimmortalized osteoblasts and osteosarcoma cell lines containing null or wild-type p53 (Kansara et al, 2009), as well as in bladder cancer cell lines containing mutant p53 (Tang et al, 2009).…”
Section: Wif1 Inhibits Cervical Cancer Growth and Invasion I Ramachansupporting
confidence: 90%
See 1 more Smart Citation
“…This inhibition of cell proliferation is consistent with the in vitro inhibition of cell growth by WIF1 as previously shown for other cancer cell lines (Ai et al, 2006;Kim et al, 2007;Kansara et al, 2009;Kawakami et al, 2009;Tang et al, 2009). However, in previous studies, WIF1 overexpression was shown to induce G 1 arrest in HPVimmortalized osteoblasts and osteosarcoma cell lines containing null or wild-type p53 (Kansara et al, 2009), as well as in bladder cancer cell lines containing mutant p53 (Tang et al, 2009).…”
Section: Wif1 Inhibits Cervical Cancer Growth and Invasion I Ramachansupporting
confidence: 90%
“…WIF1 is a secreted Wnt antagonist that is often downregulated because of genomic rearrangement, genomic loss or promoter hypermethylation in several human tumors, including colon, lung, breast, prostate, bladder, kidney and salivary gland (Wissmann et al, 2003;Byun et al, 2005;Taniguchi et al, 2005;Ai et al, 2006;Urakami et al, 2006;Queimado et al, 2008;Kawakami et al, 2009). Our study demonstrates that WIF1 downregulation is an early and widespread event in human cervical oncogenesis, which occurs frequently due to promoter hypermethylation.…”
Section: Discussionmentioning
confidence: 64%
“…Wnt ligands and FZD receptors are expressed in human breast cancer cell lines and primary tumors (30)(31)(32)(33). Multiple negative regulators of Wnt/β-catenin signaling, such as SFRP1, SFRP2, SFRP5, WIF1, DKK1, and DKK3, are down-regulated in many breast tumors (34)(35)(36)(37)(38)(39). Although Wnt/β-catenin pathway mutations are rarely detected in breast tumors, elevated levels of nuclear and/or cytoplasmic β-catenin are frequently found and are associated with poor prognosis (40).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt inhibitory factor-1 (WIF-1) is a secreted protein that antagonizes Wnt signaling (7). WIF-1 was initially detected in the human retina and highly conserved homologs have previously been described in various vertebrates (8).…”
Section: Introductionmentioning
confidence: 99%